Revisiting the taxonomy of Strobilanthes homotropa (Acanthaceae) and a new species Strobilanthes pradeepiana from the Western Ghats, India - Thomas, Sinjumol; Britto, Susai John; Mani, Bince (Phytotaxa, 2021)
Strobilanthes homotropa is an intricate species reported from Nilgiris, India. This taxon was treated in various ways leading to ambiguity in its taxonomic recognition. The present study revisits the taxonomy of S. homotropa and provides an amended description for the species. While doing so, S. homotropa is segregated from the puzzling species S. sexennis and a new species S. pradeepiana is recognized.